Comparison of the Effectiveness of Antiglaucomatous Surgeries with Various Glautex Drainage Models - I. I. Khusnitdinov; A. E. Babushkin (Oftalʹmologiâ, 2019)
Purpose: comparative study of trabeculectomy results with various models of domestic “Glautex” drainage in the surgical treatment of primary open angle glaucoma (POAG). Patients and methods. The results of surgical treatment of 98 (105 eyes) patients with POAG aged 50–83 years who underwent trabeculectomy with various Glautex drainage models were analyzed. There were 43 men (43.9 %) and 55 (56.1 %) women. The second (II) stage of POAG was diagnosed in 49 eyes (46.7 %), the third (III) stage in 56 (53.3 %). All patients were divided into 3 groups. The first (main) group consisted of 34 (37 eyes) patients who underwent trabeculectomy in combination with the implantation of Glautex DDA drainage model. The second (main) group included 29 (30 eyes) patients with trabeculectomy and implantation of the SDA model of this drainage. The third group was the control group and consisted of 35 (38 eyes) patients with the classical method of surgery without using any drainage. Results. There was a significant 71.7 % decrease in IOP compared with baseline data in the 1st patients group after antiglaucomatous surgery, 72 and 74 % decrease was in the 2nd and 3rd groups respectively (p < 0.05). An increase in IOP was noted predominantly in the control and in the second study group within 1 month of follow-up. Normalization of ophthalmotonous pressure was achieved by using needling in 13.3 % (4/30) patients in the second group, in 7.9 % (6/38) cases in the control group. The absolute hypotensive effect in the 1st group was noted in 75.7 % of cases; the relative hypotensive effect was in 8.1 %; total failure was in 16.2 %. In the 2nd group the absolute hypotensive effect of the surgery was in 73.3 % of 30 cases, the relative was in 6.7 %, total failure was in 20 %. In the control group (38 eyes), absolute success was in 63.1 %, the relative hypotensive effect was in 13.2 %, and the total failure was in 23.7 %. Conclusion. Trabeculectomy with Glautex drainage and with various models in case of primary open-angle glaucoma provided a sufficiently high relative hypotensive effect in 82 % of cases in a year after the surgery. The achieved surgery outcomes with this drainage in the studied periods did not depend on applied model: DDA or SDA (83.8 and 80 % respectively), but was higher than the classical trabeculectomy (76.3 %). However, in case of the SDA model, needling was required in 13.3 % of cases in the early postoperative period.